Regulation of Small and Medium-sized Businesses: Problems and Development Prospects - ZHETPISBAYEVA, Mukhtarima; KURMANKULOVA, Nurzhamal; MUSSATAYEVA, Assemgul; BAIGURENOVA, Mariyam; ZHANBEKOVA, Zamzegul; ARKENOVA, Zhadyra (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018DO - 10.14505//jarle.v9 2(32).37, 2018)
The article considers the current state, problems and prospects for the development of small and medium business in Kazakhstan. In the economy of any country with a market system of management, small and medium-sized businesses play an essential role. In transformational, transitional economies, which is essentially the Kazakh economy, often the role of small and medium-sized businesses is indispensable in dealing with the most acute economic and social problems. Without requiring significant expenditures from the state, small and medium-sized businesses, as a phenomenon, stabilize the social situation in the country, solving problems associated with social tension and employment of the population.